High sum-frequency generation in dielectric/antiferromagnet/Ag sandwich structures - 付淑芳 梁红 周胜 王选章 (Chinese physics B, 2014)
We present a method to increase the sum-frequency （SF） outputs in dielectric/antiferromagnet（AF）/Ag sandwich structures for a fixed input power. Two incident waves simultaneously illuminate the upper surface, one is oblique and the other is normal to it. Numerical calculations based on the SiO2/MnF2/Ag and ZnF2/MnF2/Ag structures show that the SF outputs on the upper film increase a few times as compared to those of a single AF film when the thickness of the AF film is one-quarter of the vacuum wavelength. Moreover, the SF outputs generated near the higher resonant frequency will be higher than those obtained near the lower resonant frequency. An optimum AF film thickness is achieved through investigating its effect on the SF outputs in the two different dielectric sandwich structures.